2016
DOI: 10.1080/15548627.2015.1082023
|View full text |Cite
|
Sign up to set email alerts
|

AUTEN-67, an autophagy-enhancing drug candidate with potent antiaging and neuroprotective effects

Abstract: Autophagy is a major molecular mechanism that eliminates cellular damage in eukaryotic organisms. Basal levels of autophagy are required for maintaining cellular homeostasis and functioning. Defects in the autophagic process are implicated in the development of various age-dependent pathologies including cancer and neurodegenerative diseases, as well as in accelerated aging. Genetic activation of autophagy has been shown to retard the accumulation of damaged cytoplasmic constituents, delay the incidence of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 68 publications
2
66
1
4
Order By: Relevance
“…1627 AUTEN-67 (autophagy enhancer-67): An inhibitor of MTMR14, which enhances macroautophagy. 1628 Autophagic lysosome reformation (ALR): A self-regulating tubulation process in which the macroautophagic generation of nutrients reactivates MTOR, suppresses macroautophagy and allows for the regeneration of lysosomes that were consumed as autolysosomes. 527 See also autolysosome.…”
Section: Glossarymentioning
confidence: 99%
“…1627 AUTEN-67 (autophagy enhancer-67): An inhibitor of MTMR14, which enhances macroautophagy. 1628 Autophagic lysosome reformation (ALR): A self-regulating tubulation process in which the macroautophagic generation of nutrients reactivates MTOR, suppresses macroautophagy and allows for the regeneration of lysosomes that were consumed as autolysosomes. 527 See also autolysosome.…”
Section: Glossarymentioning
confidence: 99%
“…Further evidence for autophagy’s role in preventing senescence has been found in a recent study of MTMR14, a myotubularin-related phosphatase, in antagonizing the formation of autophagic membrane structures. Blocking MTMR14 by autophagy enhancer-67 (AUTEN-67) stimulates autophagic flux and increases the lifespan of model organisms (Papp et al, 2016). …”
Section: Autophagy and Autophagy Fluxmentioning
confidence: 99%
“…It has also been shown that autophagy is activated after ICH and endoplasmic reticulum (ER) stress occur in neurodegenerative diseases . And autophagy may play different role36s in ischemic and hemorrhagic stroke . However, it is not entirely clear whether ER stress and autophagy are involved in the pathological process of ICH‐induced SBI.…”
Section: Introductionmentioning
confidence: 99%